The beneficial metabolic actions of prolactin - Macotela, Yazmín; Ruiz-Herrera, Xarubet; Vázquez-Carrillo, Dina I.; Ramírez-Hernandez, Gabriela; Martínez de la Escalera, Gonzalo; Clapp, Carmen (Frontiers in Endocrinology, 2022)
The role of prolactin (PRL) favoring metabolic homeostasis is supported by multiple preclinical and clinical studies. PRL levels are key to explaining the direction of its actions. In contrast with the negative outcomes associated with very high (>100 g/L) and very low (<7 g/L) PRL levels, moderately high PRL levels, both within but also above the classically considered physiological range are beneficial for metabolism and have been defined as HomeoFIT-PRL. In animal models, HomeoFIT-PRL levels counteract insulin resistance, glucose intolerance, adipose tissue hypertrophy and fatty liver; and in humans associate with reduced prevalence of insulin resistance, fatty liver, glucose intolerance, metabolic syndrome, reduced adipocyte hypertrophy, and protection from type 2 diabetes development. The beneficial actions of PRL can be explained by its positive effects on main metabolic organs including the pancreas, liver, adipose tissue, and hypothalamus. Here, we briefly review work supporting PRL as a promoter of metabolic homeostasis in rodents and humans, the PRL levels associated with metabolic protection, and the proposed mechanisms involved. Finally, we discuss the possibility of using drugs elevating PRL for the treatment of metabolic diseases.